286 Maternal systemic lupus erythematosus and the risk of cryptorchidism in male offspring. (April 2019) - Knudsen, Signe Schollhammer; Bech, Bodil Hammer; Deleuran, Bent Winding; Ramlau-Hansen, Cecilia Høst; Arendt, Linn Håkonsen
Abstract : Background: Background: Systemic lupus erythematosus (SLE) is one of the most prevalent autoimmune rheumatic diseases affecting young women of childbearing age. The disease is characterized by elevated levels of systemic inflammation and high levels of circulating autoantibodies, potentially affecting multiple organs and tissues. Women suffering from SLE have decreased fecundity, and increased risk of adverse pregnancy outcomes such as miscarriage and preeclampsia. This risk is further elevated with increasing disease activity, and seems less pronounced when disease is well managed. SLE is not in itself considered a risk factor for specific birth defects; however, not all congenital anomalies are diagnosed immediately after birth, and might thus be overlooked in most studies on reproductive outcomes. Cryptorchidism (undescended testis) is a common genital anomaly, often diagnosed throughout childhood. It arises from an imperfect genital development in the foetus. As the prevalence of cryptorchidism in male offspring is higher when their mothers are suffering from preeclampsia or gestational diabetes, we aimed to investigate if a similar association exists between maternal SLE and cryptorchidism in the offspring. Methods: Methods: We conducted a nationwide study including all male singleton live births in Denmark from 1995 to 2016. Using the Danish nationwide population based registers, we assessed the occurrence of cryptorchidism according to prenatal disease-state of the mothers (SLE/no SLE). Cryptorchidism was assessed as both any diagnosis of cryptorchidism and diagnosis of cryptorchidism and corrective surgery. Using Cox proportional hazards models we calculated hazard ratios (HRs), accounting for varying age at time of diagnosis, and adjusting for maternal age, smoking during pregnancy, pre-gestational BMI, parity, educational level and ethnicity. Results: Among 6 90 240 boys, 352 boys were born of mothers with pre-existing SLE. Of those, 15 (4.3%) boys were diagnosed with cryptorchidism, and seven boys (1.9%) underwent corrective surgery. We found an adjusted HR of 1.68 (95% CI: 1.01, 2.78) for cryptorchidism and 1.46 (95% CI: 0.69, 3.06) for cryptorchidism with corrective surgery, among boys born by mothers with SLE, compared with unexposed boys. This is consistent with an increased risk of cryptorchidism among the exposed boys, even though the relatively few exposed cases limits the precision of the estimates. Conclusions: Conclusions: Boys exposed to maternal SLE appears to have higher risk of cryptorchidism, compared with unexposed boys. Funding Source(s): Aarhus University, the Danish rheumatism society and Karen Elise Jensen foundation.